Learning Curve of Total Hip Arthroplasty in Direct Anterior Approach without Requiring Corrective Osteotomy for Hip Dysplasia. Issue 5 (7th April 2022) - Shen, Kaiwei; Feng, Eryou; Lin, Feitai; Weng, Yan; Chen, Jinhua
Abstract : Objective: To explore the learning curve of total hip arthroplasty in direct anterior approach (DA‐THA) without requiring corrective osteotomy for patients with unilateral developmental dysplasia of the hip (DDH) through the evaluation of clinical and radiographic results. Method: From December 2015 to January 2021, we retrospectively evaluated a surgeon's first 100 patients with unilateral hip dysplasia (Crowe I‐III) who underwent DA‐THA. All procedures were performed by a fellowship‐trained joint surgeon. Cementless hemispheric porous‐coated acetabular cups and tapered cementless stems were used in all hips. The radiographic data, including leg length, the height of the center of rotation, femoral head offset, the cup anteversion and inclination angle, were measured. The cumulative sum analysis (CUSUM) and risk‐adjusted cumulative sum analysis (RA‐CUSUM) were used to determine the learning curve of DA‐THA for each patient's operation time. By analyzing the operation time, complication rate, postoperative length of hospitalization and creatine kinase (before surgery and the third day after surgery), estimated blood loss, Harris score, radiographic data were compared between the different stages of the learning curve. Results: The mean follow‐up time was 35.45 ± 16.82 months. The CUSUM method obtained the maximum turning point of the curve at 43 cases, which divided the learning curve into Learning Period and Mastery Period. The CUSUM learning curve was best modeled as a cubic curve with the equation: CUSUM (min) = 0.001 x 3  − 0.495x 2  + 33.60 x  − 10.00, which had a higher R 2 value of 0.967. The pre‐operative data, creatine kinase, estimated blood loss and postoperative Harris scores of the two stages were not statistically significant ( P  > 0.05). The mean operation time was 118 min in the Learning Period and 87 min in the Mastery Period. Statistically significant differences were detected in the operation time ( P  < 0.001), postoperative length of hospitalization( P  = 0.024), and postoperative leg length discrepancy ( P  = 0.012) between the two stages. The overall complication rates were 27.9% in the Learning Period and 12.3% in the Mastery Period ( p  = 0.049). The overall outliers of radiographic data were 34 cases in the Learning Period and 31 cases in the Mastery Period (79.07% vs 54.39%, P  = 0.010). Conclusions: The DA‐THA is a valuable alternative to achieve satisfactory clinical results for mild‐to‐moderate DDH patients. Furthermore, accurate analysis of the learning curve of DA‐THA for hip dysplasia by the CUSUM method showed that the surgeons need to finish about 43 cases to master the technique. Abstract : We used the cumulative sum analysis to obtain the learning curve of first 100 patients with unilateral hip dysplasia who underwent total hip arthroplasty in direct anterior approach without requiring corrective osteotomy. Surgeons need to finish about 43 cases to master the technique in terms of operative time, complication rate, and radiographic data.